Image‐based simulation of urethral distensibility and flow resistance as a function of pelvic floor anatomy. Issue 7 (3rd May 2014) - Yao, Franklin; Laudano, Melissa A.; Seklehner, Stephan; Chughtai, Bilal; Lee, Richard K.
Abstract Aims The goal of this study is to develop an image‐based model of urethral distention and resistance in women with and without SUI. Methods A biomechanical vector force model was created to simulate the mechanical deformation of pelvic floor structures during cough and Valsalva in order to measure urethral distension and predict flow resistance patterns. Dynamic MRI images were used to create a spatial model to construct an accurate representation of tissue thickness and location, which was combined with tissue property values (MATLAB 2011a, MathWorks, Natick, MA). Spatial profiles were created to demonstrate the effects of hypermobility and tissue property variability on distensibility and flow resistance along the urethra. Sensitivity analyses were conducted to demonstrate the relationship between flow resistance and various tissue properties. Results The average distension for incontinent cases (3.8 mm) was significantly greater than that of continent cases (2.6 mm) (t = 3.3083, df = 8, P < 0.01), corresponding to a 70% drop in average resistance to urine flow. Sensitivity analyses demonstrated that the stiffness and contractility of the vagina and urethra had the greatest effect on continence. Conclusions We present a novel, 2‐dimensional biomechanical model of female stress urinary incontinence (SUI) that relates the effects of various factors such as tissue elasticity, pelvic floor structure, and muscle activation. A better understanding of the pathophysiology underlying SUI has potential implications for the creation of novel targeted treatments. Neurourol. Urodynam. 34:???–???, 2015. © 2014 Wiley Periodicals, Inc.